Non-Sustained Ventricular Tachycardia in A Child After Lightning Strike - Haşim Olgun; Naci Ceviz (Güncel Pediatri)
Lightning strike is a rare natural phenomenon with a high risk of fatality. The most dramatic complications of lightning injury are those associated with the cardiovascular system, and cardiac arrest is the primary cause of death. Rhythm problems often lead to death in the acute phase of lightning strike, but recording rhythm problems in the acute phase is very difficult. We described a child who suffered a lightning strike and developed cardiac arrest shortly after admission to the emergency department. He had transient ischemic electrocardiogram (ECG) changes and non-sustained ventricular tachycardia (VT) on Holter monitoring and was treated with lidocaine.